Nepetalactones and other constituents of Nepeta nuda ssp. albiflora - Kökdil, G; Yalçin, SM; Topçu, G (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY, 1999)
The hexane extract of Nepeta nuda ssp. albiflora led to the isolation of six known monoterpene nepetalactones, 4a alpha, 7 alpha,7a alpha-nepetalactone (1), 4a alpha, 7 beta,7a beta-nepetalactone (2), 4a beta,7 alpha,7a beta-nepetalactone (3), 4a beta,7 alpha,7a alpha-nepetalactone (4), 4a alpha,7 beta,7a beta-nepetalactone (5), 3 alpha-hydroxy-4a alpha,7 alpha,7a alpha-dihydronepetalactone (=nepetalic acid) (6) and a dimeric 5,9-dehydronepetalactone (7) along with two known steroids beta-sitosterol and sitosterol 3-one and a triterpene betulinic acid. The acetone extract of the same plant afforded compound 7 in a higher yield in addition to compounds 2 and 6, and sesquiterpene caryophyllene oxide, the iridoid glucoside 1,5,9-epideoxyloganic acid, the triterpenoids oleanolic, ursolic and betulinic acids, and sitosterol 3 beta-glucoside.
Keywords: Nepeta nuda ssp. albiflora; Lamiaceae; nepetalactones; dimeric 5,9-dehydronepetalactone; sesquiterpene; triterpenoids; steroids; STEREOCHEMISTRY; CATARIA; Chemistry; Engineering